Scattering of elastic surface waves on a localized mechanical load of the surface - A. DUKATA; J. KAPELEWSKI (Archives of Acoustics, 2014)
This paper presents a model of scattering of elastic surface waves (ESW) on a single reflective elements of dot structures loading the surface of a hexagonal structure with a sixfold rotation axis, normal to the plane of propagation. Qualitative results obtained with the use of TIERSTEN type boundary conditions [7] and reduced Green's functions presented by MARADUDIN and DOBRZYŃSKI [14] are given for a rectangular dot. Resultant components of the scattering amplitude were achieved with the utilization of an approximation of the stationary phase and approximation of far distances.